Penerapan Model Pembelajaran Project Based Learning Materi sanitasi Hygiene Serta K3 Pada Peserta Didik Kelas X Tata Kecantikan Kulit Dan Rambut SMKN 1 Sooko Mojokerto - Eka Rizki Nur Izzah; Mutimmatul Faidah; Dewi Lutfiati; Octaverina Kecvara Pritasari (Jurnal Tata Rias, 2024)
The activity of students in learning is still not optimal. To overcome this problem, it is important to apply the right learning model. This research aims to examine the implementation of project-based learning, as well as analyse the improvement of learning outcomes and student responses. The type of research carried out is Class Action Research (PTK). The subject of this research consists of 34 students in class X Skin and Hair Beauty at SMKN 1 Sooko, Mojokerto. Instruments used in research include: 1) observation instruments to assess the learning process; 2) test instruments that include data presentation and drawing conclusions or meaning. The results of the research show that: 1) the implementation of project-based learning took place for a maximum of two cycles, with a percentage of 100%; 2) there was a significant increase in cognitive learning results from cycle I to cycle II, namely from 15.63% to 43.75%, while the student project results also increased from 18.75% to 78.13%; 3) the student response to project-based learning showed a positive response, reflected by a decrease in the percentage in the 'less' category and an increase of 6.25% in the 'good' category, and a decrease of 5.25% in the 'less' category. In conclusion, the implementation of project-based learning has a positive impact on the improvement of student learning outcomes, and this can be seen from the better response from learners between cycle I and cycle II